Marketing Strategy Analysis in Automotive UMKM " Showroom Car Used "Gatra Jaya Mobilindo" in Bandar Lampung - Daud, Syahril; Alfaris, Jihad Sulthan; Patrisia, Ratih Ayu; Nadia, Rifatul (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This study aims to analyze the marketing strategy of automotive UMKM Gatra Jaya Mobilindo Car Showroom in Bandar Lampung. By identifying the strengths, weaknesses, opportunities, and threats faced by the showroom in a dynamic business environment. Qualitative descriptive research methods and data collection using interviews, observations needed by researchers, then SWOT Analysis is carried out. Based on the SWOT strategy analysis, Gatra Jaya Mobilindo Showroom can maximize its strengths and opportunities by utilizing a competent sales team to actively interact with customers, both directly and through social media, and promote product quality advantages compared to competitors. Strategic location is also an important asset that can be utilized by installing banners to attract consumer attention. In overcoming weaknesses, showrooms need to improve customer comfort through friendly and professional service and ensure product quality that does not disappoint. To deal with threats, showrooms can strengthen branding through creative content on social media, provide incentives to loyal customers, and innovate in the buying and selling process. These strategies are expected to help Gatra Jaya Mobilindo Showroom increase its competitiveness in the market.